Advanced Graphene-Based Technologies for Antibiotic Removal from Wastewater: A Review (2016–2024) - Joydip Sengupta; Chaudhery Mustansar Hussain (C)
The increasing presence of antibiotics in wastewater poses significant environmental risks, including the promotion of antibiotic resistance and harm to aquatic ecosystems. This study reviews advancements in graphene-based technologies for removing antibiotics from wastewater between 2016 and 2024. Graphene-based platforms, such as graphene oxide (GO), reduced graphene oxide (rGO), and graphene composites, have shown great promise in this field because of their exceptional adsorption capacities and rapid photocatalytic degradation capabilities. Functionalized graphene materials and graphene integrated with other substances, such as metal oxides and polymers, have enhanced performance in terms of antibiotic removal through mechanisms such as adsorption and photocatalysis. These technologies have been evaluated under various conditions, such as pH and temperature, demonstrating their practical applicability. Despite challenges related to scalability, cost-effectiveness, and environmental impact, the advancements in graphene-based technologies during this period highlight their significant potential for effective antibiotic removal, paving the way for safer and more sustainable environmental management practices.